Non Conviction Based (NCB) Asset Forfeiture for Recovering the Corruption Proceeds in Indonesia - PRIYATNO, Dwidja (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The success in recovering asset stolen from corrupt practices was one of the key success indicators in an attempt to eradicate corruption in Indonesia. The transnational corruption trend which involved many actors has made the asset recovery efforts to be more difficult. This article aimed to investigate the asset recovery efforts, the role of state institutions and the law enforcement officers in the assets recovery effort. The research method used was normative legal research, which was done by examining the secondary data in which the data were analyzed qualitatively. The conclusion derived in this article was that the Non Conviction Based (NCB) Asset Forfeiture is a critical tool for recovering the proceeds of corruption and also to combat corruption, especially in case where the proceeds have been transferred abroad. However, to ensure that such measure would be a strategic policy, it would be necessary to enter into international treaties with other countries related to the corruption case. In addition, the harmonization of Indonesian Anti-Corruption Law regarding the Eradication of Criminal Acts of Corruption should be conducted in order to support the Non Conviction Based (NCB) Asset Forfeiture. The NCB asset forfeiture system should encompass the 36 Key Concepts introduced in StAR so that the NCB system could be more effective in recovering the stolen assets.